1985
DOI: 10.1159/000183520
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Hypertonic Dialysis

Abstract: We have investigated the usefulness and practicability of the so-called sequential hypertonic dialysis in 2 selected patients with severe hemodialysis-induced hypotension; 190 mmol/l of sodium dialysate during the 1st and 3rd h and 132 mmol/l throughout the 2nd and 4th h were used, with a Drake-Willock-Bi proportionating unit, which was electronically modified for the purpose of the study. Crossover was made, patients serving as their own controls in two consecutive cycles: 3 weeks conventional hemodialysis fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
1

Year Published

1988
1988
2003
2003

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…To minimize the effect of blood volume reduction as one of the contributing factors, it is extremely important to carefully observe the distribution of fluids and sodium [3, 4, 5, 6, 7, 8, 9]. The sodium dialysate concentration has often been increased so as to obtain intradialytic cardiovascular stability [10].…”
Section: Introductionmentioning
confidence: 99%
“…To minimize the effect of blood volume reduction as one of the contributing factors, it is extremely important to carefully observe the distribution of fluids and sodium [3, 4, 5, 6, 7, 8, 9]. The sodium dialysate concentration has often been increased so as to obtain intradialytic cardiovascular stability [10].…”
Section: Introductionmentioning
confidence: 99%
“…For these purposes, the sodium in the dialysis fluid follows a time‐dependent profile over the course of the session, including high‐sodium dialysis periods to maintain the patient's intravascular blood volume and low‐sodium dialysis periods to compensate for the excessive sodium gain 1 . In spite of this low‐sodium dialysis period, many reports indicate that the sodium profiling haemodialysis shows shortcomings of the chronic sodium load, which presents as elevated postdialysis serum sodium concentration and as thirst, excessive weight gain, or hypertension during interdialytic period 2–10 …”
Section: Introductionmentioning
confidence: 99%
“…This can be adjusted manually or automatically using computer controlled profiles available on many dialysis delivery systems. Studies of sodium profiling generally have shown a reduction in intradialytic symptoms but at the expense of increased symptoms between dialysis treatments (2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%